Isolation and Characterization of Chelonia mydas Myoglobin - MOHAMAD SADIKIN; RINI PUSPITANINGRUM; SEPTELIA INAWATI WANANDI; RONDANG ROEMIATI SOEGIANTO (HAYATI Journal of Biosciences, 2012)
Green sea turtle – Chelonia mydas is a lung respiration animal that is able to dive and stay uder sea water for hours without needing to surface for oxygen. As oxygen supply in muscles is assured by myoglobin, we propose to study some characteristic of this muscle protein in green sea turtles. To achieve this objective, pure green sea turtle myoglobin has to be made available. Therefore, our first task is to purify this muscle protein from green sea turtles. Skeletal muscles from 3 green sea turtle hatchlings were studied microscopically and biochemically. Microscopy observation showed a general structure of striated muscle. Biochemical studies revealed that green sea turtle myoglobin could be more purely isolated to a certain degree by Sephadex G-75 gel filtration and purified by immunoaffinity gel chromatography rather than direct purification by DEAE-Sepharose ion exchange chromatography technique. SDS-PAGE analysis showed that green sea turtle myoglobin ran together with horse myoglobin as 17 kDa molecular weight proteins